2022
DOI: 10.1101/2022.03.22.485384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global, regional, and cryptic population structure in a high gene-flow transatlantic fish

Abstract: Lumpfish (Cyclopterus lumpus) is a transatlantic marine fish displaying large population sizes and a high potential for dispersal and gene-flow. These features are expected to result in weak population structure. Here, we investigated population genetic structure of lumpfish throughout its natural distribution in the North Atlantic using two approaches: I) 4393 genome wide SNPs and 95 individuals from 10 locations, and II) 139 discriminatory SNPs and 1,669 individuals from 40 locations. Both approaches identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 117 publications
1
2
0
Order By: Relevance
“…Admittedly, our analysis lacks samples from along the Nova Scotia coast which would help resolve the cline in the region of transition. This study extends previous work on lumpfish in the Northwest Atlantic which uncovered a major delineation between Greenland and all sites south of Greenland (Garcia‐Mayoral et al, 2016; Pampoulie et al, 2014), and suggested possible discreteness between the two Gulf of St. Lawrence (Canada) and two Gulf of Maine (USA) sites (Jansson et al, 2022). The accumulating evidence strongly supports regional scale population structure in this species.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Admittedly, our analysis lacks samples from along the Nova Scotia coast which would help resolve the cline in the region of transition. This study extends previous work on lumpfish in the Northwest Atlantic which uncovered a major delineation between Greenland and all sites south of Greenland (Garcia‐Mayoral et al, 2016; Pampoulie et al, 2014), and suggested possible discreteness between the two Gulf of St. Lawrence (Canada) and two Gulf of Maine (USA) sites (Jansson et al, 2022). The accumulating evidence strongly supports regional scale population structure in this species.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, site fidelity of adults and their life history/local oceanographic conditions seems to allow the isolation of lumpfish across large and small spatial scales. A recent study found that sampling that took place at breeding sites or within juvenile groups, formed clear‐cut groups, while sampling of actively migrating individuals were more admixed (Jansson et al, 2022), implying that discrete population structure could potentially be linked to homing behavior. Lumpfish have several life history traits aside from homing that could also contribute to local adaptation, including eggs that are generally attached to an inshore substrate, such as rocks (Goulet & Green, 1988), a juvenile stage which adheres to inshore seaweed by way of their pelvic adhesive disk for up to a year (Sheehan et al, 2012; Vandendriessche et al, 2007), and an adult stage which often adheres to solid objects such as lobster pots and rocks to keep from drifting (COSEWIC, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The work was performed at the Institute of Marine Research, Bergen Norway ( www.hi.no ) and within the Linnaeus Centre for Marine Evolutionary Biology ( www.cemeb.science.gu.se/ ). Earlier versions of this manuscript have previously been published in a thesis [ 132 ] and as a preprint in bioRxiv [ 133 ]. We are grateful for all the feedback and reviews we have received of this article and earlier versions thereof.…”
mentioning
confidence: 99%